Transformasi Gaya Bahasa Pada Lagu Anggun C Sasmi Dalam Bahasa Perancis dan Bahasa Indonesia - Sari, Eka Nurita; Diana Rosita; Indah Nevira Trisna (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2024)
The research has three purposes the first is to describe the figure of speech of the French languages and Indonesia langues from Anggun C Sasmi song, and the second is to explain the change in the figure of speech in the Anggun Sasmi song that has two languages versions and the last one of implications for learning French literature. The method used in this study is descriptive-qualitative. The data used are lyrics in Anggun C. Sasmi's songs in both French and Indonesian. The method of data collection are metode simak, and technique (SBLC) Simak Bebas Libat Cakap and metode dokumentasi. To analyze the data, the writer uses the method analyze data qualitative it belongs Miles and Huberman. In this study, validity uses semantic validity and inter-rater rehabilitation. The results of this study Anggun C Sasmi more often uses a figure of speech for comparison. At the time of making the song, Sasmi was very attentive to the beauty of her lyrics. Then the result of the transformation figure of speech for lyrics from Anggun C Sasmi of French languages and Indonesian languages do not have much in common. This research can provide implications in linguistic learning for intermediaries.